Partner models of explainers: a qualitative interview study - Gladow, Viviane; Buhl, Heike M. (Frontiers in Education)

Conceptualising Risk and Risk Literacy—results of a Delphi Study Konzeptualisierung von Risiko und Risikokompetenz – Ergebnisse einer Delphi-Studie - Eichler, Andreas; Büchter, Theresa; Binder, Karin (Journal für Mathematik-Didaktik)
Abstract Risk is an integral part of modern societies and therefore school education, and in particular mathematics education, should develop students’ risk literacy. Students’ risk literacy is part of the interdisciplinary research project siMINT (Understanding complex STEM topics: Using simulations to promote competences for the 21st century). One first challenge in this project was to find a common ground for the inconsistently conceptualised terms of risk and risk literacy. Consequently, the aim of this paper is to contribute to the conceptualisation of risk and risk literacy. The first part of this paper provides a literature review on these areas, resulting in a working conceptualisation of the two concepts. We further carried out two consecutive steps of a Delphi study with N = 15 and N = 12 experts respectively, to develop a common conceptualisation based on the plurality of different dimensions and elements of risk and risk literacy. Based on the results of the first step of the Delphi study, we modified our working conceptualisation, using a common model of risk and risk literacy with different dimensions. In the second step of the Delphi study, the experts comment on (i) the dimensions and (ii) the elements of risk and risk literacy in these dimensions. The results showed that the experts are able to locate their individual definitions of risk in the model with three dimensions (relation between risk/uncertainty, connotation, and mathematical object) that we developed and to formulate reasons for their allocation. Furthermore, the results revealed that risk literacy consists of subsets of mathematical and non-mathematical elements that the experts rate differently with regard to their importance. In general, the results contribute to clarifying the constructs of risk and risk literacy as a basis for developing approaches to improve risk literacy.

Evaluation des Buddy-Programms der GDCP-Jahrestagung 2025 - Zwick, Linda; Bühler, Eva; Weiler, David Christoph (KI in der naturwissenschaftlichen Bildung)
Der Erfolg von Wissenschaftler:innen in frühen Karrierephasen (WiKa) hängt von vielen Faktoren ab, wobei die wissenschaftliche Gemeinschaft ein entscheidender Faktor sein kann (Cornér et al., 2018; Corceslles et al., 2019; Corcelles-Seuba et al., 2023). Vor diesem Hintergrund ist es wichtig, dass die wissenschaftliche Gemeinschaft gezielte Unterstützungsangebote für WiKa bereitstellt, in denen sie neben dem fachlichen Austausch auch Möglichkeiten zur Vernetzung und sozialen Unterstützung haben. Die WiKa der GDCP haben 2023 mit dem Buddy-Programm auf der Jahrestagung begonnen, um Wissenschaftler:innen zu Beginn ihrer Promotionszeit ein strukturiertes Unterstützungsangebot bereitzustellen. Das Buddy-Programm wurde in den folgenden Jahren basierend auf den Rückmeldungen der Teilnehmenden weiterentwickelt. In diesem Beitrag werden die Evaluationsergebnisse des Buddy-Programms während der Jahrestagung 2025 vorgestellt und diskutiert.
Keywords: GDCP; Buddy-Programm; Evaluation

The integration of probability-based arguments in risk-related contexts - Büchter, Theresa; Binder, Karin; Eichler, Andreas (Proceedings of the IASE 2025 Satellite Conference - Statistics and Data Science Education in STEAM)

Simulationen in der MINT-Bildung - Impulse für den Mathematikunterricht (Der Mathematikunterricht)

The role of social-emotional competencies for children’s cooperative learning processes in inclusive primary school classrooms. Individual Oral Presentation. 5th Porto International Conference on Research in Education (ICRE) 2026. - Hellmich, Frank; Knickenberg, Margarita; Funk, Michael; Casamassima, Gianna; Löper, Marwin Felix

Predictors of primary school students’ prosocial behaviour toward peers with social-emotional difficulties in inclusive education: Insights from the Theory of Planned Behaviour. Individual Oral Presentation. 5th Porto International Conference on Research in Education (ICRE) 2026. - Löper, Marwin Felix; Hellmich, Frank

Unterschiedliche Typen von Simulationen - Klassifikation, Beispiele und unterrichtlicher Einsatz - Büchter, Theresa; Binder, Karin; Eichler, Andreas (Der Mathematikunterricht)

Entwicklung einer wärmebildkamerabasierten Temperaturmesseinrichtung im Lasersinterverfahren - Azam, Mohammad Hamid

Early postural dynamics reveal the rapid processing of fake social cues for deceptive actions in sports - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Schmidt, Thomas; Weigelt, Matthias (Scientific Reports)
Abstract Deceptive actions such as head fakes are a hallmark of interactive sports, yet it is not well understood how decisions and whole-body responses to head fakes unfold over time. In the present study, participants viewed video sequences of a basketball player passing to the left or right, either with or without a head fake. In the buzzer task, participants moved laterally to press a response button as if to intercept the pass. In the vocal task, they verbally indicated pass direction. Reaction times (RTs), movement times (MTs), and medio-lateral center-of-pressure (CoP) displacements were recorded to investigate whether motor output is rapid and stimulus-driven or rather requires continuous integration of fake and pass cues. Further, we investigated whether the mere observation of a basketball player leads to overt micromovements even if no response movement is intended. The data analysis shows that head fakes increased RTs in both the buzzer and vocal tasks. In the buzzer task, head fakes induced an initial, small erroneous CoP shift, which was then rapidly corrected. When CoP trajectories were aligned by head orientation, fake and non-fake trajectories diverged shortly after movement onset. In the present dynamic sport-related context, this pattern is more compatible with the early integration of head and pass information than with a strictly sequential prime-target account, although the paradigm differs from classic Rapid Chase Theory designs with discrete primes and target events. In the vocal task, participants were not instructed to move, yet CoP traces showed tiny but systematically lateralized micromovements with a temporal structure resembling that in the buzzer task, albeit without an initial erroneous shift for head fakes. These postural fluctuations are consistent with action-observation-related motor activation, although they do not uniquely identify motor resonance and may also reflect attentional or generalized embodied response tendencies. A clear deceptive response conflict at the postural level emerged only when a lateralized action was prepared.

Global solutions and large time stabilization in a model for thermoacoustics in a standard linear solid - Black, Tobias; Winkler, Michael (Evolution Equations and Control Theory)

Krise oder Rekonfiguration? - Scharlau, Ingrid (Forschung und Lehre)

Characterization of spatial Schmidt modes in high-gain SU(1,1) interferometers - Scharwald, Dennis; Sharapova, Polina (Physical Review Research)
Multimode quantum light has promising applications in many areas of physics, such as quantum communications and quantum computing. However, its multimode nature also makes it challenging to measure its properties. Recently [I. Barakat et al., Optica Quantum 3, 36 (2025)], a technique for the simultaneous measurement of squeezing of multiple broadband modes based on a phase-sensitive amplification approach was experimentally implemented using a setup that effectively corresponds to an SU(1,1) interferometer. Here, we aim to provide a complete theoretical analysis of the modal structure of (generally unbalanced) SU(1,1) interferometers and a detailed theoretical formal derivation of the framework for this technique. Utilizing the joint Schmidt decomposition of the transfer functions, we investigate the shape and phase profiles of the modes of the SU(1,1) interferometer and its components [parametric down-conversion (PDC) sections] for different parametric gain regimes. We discover a complicated interplay between the PDC modes and the modes of the entire interferometer, and analyze it by using their overlap coefficients as a similarity measure. Finally, we develop a rigorous processing method for the aforementioned multimode squeezing measurement technique and discuss necessary approximations to make this method experimentally feasible.

Professionalisierung angehender Lehrpersonen für Sprachbildung mittels Unterrichtsvideos. Eine qualitative Inhaltsanalyse von Studierendentexten - Dehn, Freya (die hochschullehre)

Deutsch als Zweitsprache, Sprachbildung und Mehrsprachigkeit: Curriculare Grundlagen für die Professionalisierung von Lehrkräften - Minova, Milena; Maahs, Ina-Maria; Dehn, Freya; Drews, Kathrin; Vieth, Brenda; Böttger, Lydia; Heine, Lena; Niederhaus, Constanze; Roll, Heike; Roth, Hans-Joachim

Corporate resilience through generic AI-based workflows in strategic product planning - Özcan, Deniz; Gräßler, Iris (1st International Symposium: March 24 – 26, 2026, Heinz Nixdorf Institute, Paderborn University)
In increasingly volatile and uncertain markets, corporate resilience has become a critical capability in strategic product planning. Companies face significant challenges in systematically monitoring and interpreting heterogeneous environmental data originating from diverse sources, formats, and temporal contexts. While predefined workflows and decision trees can support strategic analysis, they often lack the flexibility required to cope with dynamic market conditions and foresightrelated data from extreme dispersed and heterogeneous sources. This paper proposes a method to enhance corporate resilience through the application of generic, reusable AI-based workflows in strategic product planning. The approach integrates Data Science and Artificial Intelligence methods into modular, visually modelled workflows that enable hybrid human-AI decision-making. Based on a systematic literature review and an analysis of industrial challenges, key success factors and resilience criteria are identified. These insights are used to develop a method that supports internal and external analyses, scenario-based strategy development, and adaptive implementation monitoring within a generic workflow structure. The method leverages techniques such as machine learning and generative AI to process structured and unstructured data, identify patterns, and support real-time strategic assessments. Validation with decision-makers from medium-sized companies demonstrates improved transparency, repeatability, and cross-functional collaboration compared to predefined workflows.

The Words of Jesus and Scriptural Hermeneutics in the Qur’an - Ghaffar, Zishan (Islam and Christian–Muslim Relations)
This article examines the most frequently attributed statement of Jesus in the Qur’an, namely, ‘God is my Lord and your Lord’ (Q 19:36; Q 43:64; Q 3:51; Q 5:72; Q 5:117). It investigates the extent to which this formula is connected to Jesus’s words to Mary Magdalene on Easter morning in John 20:17. The analysis aims to show that the Qur’an critically engages with the Christian interpretive tradition surrounding this statement as recorded in John’s Gospel and adapts it – both contextually and verbally – within its own theological framework. As in the Christian tradition, this Qur’anic engagement also generates a broader discourse on the hermeneutics of scriptural interpretation.
Keywords: Qur’an; John 20:17; Scriptural hermeneutics; Words of Jesus; Intertextuality

Hybrid decision support in strategic product planning - Gräßler, Iris; Goldstein, Julius Hendrik (1st International Symposium: March 24 – 26, 2026, Heinz Nixdorf Institute, Paderborn University)
Strategic product planning defines foresighted directions for product engineering by determining which ideas, technologies and concepts are pursued further. Decisions made in this phase strongly influence subsequent life cycle phases but are characterized by high uncertainty, fragmented information, and predominantly qualitative assessment practices. At the same time, increasing digitalization generates large, heterogeneous, and dynamic data from markets, engineering, usage, and sustainability domains. In this work, such information is understood as extreme data, as its heterogeneity, variety, and dynamics exceed the capabilities of traditional planning approaches. This paper investigates the potential of leveraging extreme data to strengthen hybrid decision support in strategic product planning. A structured literature review is conducted to identify key challenges. These challenges are analysed along the generic product life cycle to capture decision points, information flows, and information circularity. Relevant data sources are identified with respect to their relevance for strategic decisions. Based on this analysis, seventeen potentials for hybrid decision support are derived and clustered into five fields of action. The results indicate that extreme data can enhance strategic foresight, idea evaluation and portfolio decisions, lifecycle-spanning knowledge integration, engineering support for strategic decisions, and the adoption of AI-based methods.

Multi-Objective Pipeline Optimisation and Configuration of Automatic Train Operation Trajectories - Mensendiek, Carolin; Zeipel, Henrik; Preuß, Oliver Ludger; Seiler, Moritz; Sextro, Walter; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference Companion)

Digitaler Faschismus und digitaler Kapitalismus - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)